Demographic Characteristics and Turnover Intention : A Study of Indian BPOs - Afroz, Saman; Haque, Mohammad Israrul (Prabandhan: Indian Journal of Management, 2021)
The purpose of the present study was to determine the relationship between the demographic characteristics and turnover intention of employees in the Indian business process outsourcing (BPO) sector. The study considered employees’ demographic characteristics such as gender, marital status, age, monthly income, and shifts to determine their relationship with turnover intention. The data collected comprised of 453 BPO employees belonging to the lower and middle levels in organizations. The analysis exhibited mixed results. Demographic characteristics like gender and marital status showed no statistically significant relationship with turnover intention. However, factors like age, monthly income, and shifts confirmed a statistically significant relationship with turnover intention among the BPO professionals. Young BPO employees at the entry-level positions had a higher intention to quit than the older ones. Similarly, lower-income group employees were less likely to stay with their current organizations. The study revealed that employees engaged in the afternoon and night shifts had more propensity to leave their current employers than those working in the morning shifts.